2007
DOI: 10.1186/1471-213x-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B1 plays a redundant role during mouse development and in tumour angiogenesis

Abstract: Background: Plexins are a large family of transmembrane receptors for the Semaphorins, known for their role in the assembly of neural circuitry. More recently, Plexins have been implicated in diverse biological functions, including vascular growth, epithelial tissue morphogenesis and tumour development. In particular, PlexinB1, the receptor for Sema4D, has been suggested to play a role in neural development and in tumour angiogenesis, based on in vitro studies. However, the tissue distribution of PlexinB1 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 42 publications
1
59
1
Order By: Relevance
“…When Sema4D levels were reduced with shRNA-expressing lentiviruses, this pro-angiogenic phenotype was greatly attenuated, though it should be noted not totally blocked. This could be due to functional redundancy for Sema4D/Plexin-B1-mediated angiogenesis, which has been observed in a knock-out study (23), and the fact that HIF-1␣-overexpressing cells still produce other proteins that are components of the hypoxia response and could promote angiogenesis, such as VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…When Sema4D levels were reduced with shRNA-expressing lentiviruses, this pro-angiogenic phenotype was greatly attenuated, though it should be noted not totally blocked. This could be due to functional redundancy for Sema4D/Plexin-B1-mediated angiogenesis, which has been observed in a knock-out study (23), and the fact that HIF-1␣-overexpressing cells still produce other proteins that are components of the hypoxia response and could promote angiogenesis, such as VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…1E). To confirm our results further, particularly in the light of a recent contradictory publication (Fazzari et al, 2007) that has reported plexin B1 expression in the mesenchyme, we took advantage of a mouse line expressing the reporter gene product β-galactosidase under the control of the plexin B1 promoter (Plxnb1lacZ). This knock-in reporter reflects closely the developmental expression pattern of plexin B1 in the nervous system, because the entire promoter elements of the Plxnb1 gene are available to direct lacZ expression (Friedel et al, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…37 The plexin-B1 knockout mouse was recently reported. 41 The mice appear to develop normally. Studies on their platelets are pending.…”
Section: Receptor-ligand Interactions At the Junctions Between Plateletsmentioning
confidence: 99%